The Rating System as Part of the American Film Industry (1970–2019) - Lewicki, Arkadiusz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The article is an attempt to indicate what role the rating system introduced in 1968 plays in the American film industry. The first part provides an introduction to the history of American film censorship and presents the reasons why the Production Code was replaced by a system of restrictions related to the age of viewers. The second part of the text is analytical in nature. First, the distribution of individual rating categories in the 500 most popular films from 1970–2019 is checked, and it is revealed how the understanding of individual categories has changed and how the US film industry itself has changed. The second study, based on statistical data, shows the distribution of rating categories among all films distributed in the US in the years 2000–2019. This allows us to indicate the growth in the importance of the PG and PG-13 categories and also the increase in both the number and market share of films that are not subject to the system introduced by the MPA.